(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The importance of strategic management lies in the fact that it provides an excellent framework for organizing and directing organizational behavior, in the sense that it affects the workers and forms the patterns of their behavior that they are required to follow within the organization in which they work. And players working in the central federations of the Iraqi Olympic Committee). The researcher conducted her study on a sample of 124 players and coaches representing 8 clubs in Babil Governorate, and they were divided into an exploratory sample, a preparation sample, and an application sample, through which the strategic management scale for the administrative bodies of the clubs was prepared. The levels and extents of the strategic management of the administrative bodies were extracted according to the perspective of the players and coaches working in the clubs, and it was on five levels, namely (the weak level, the acceptable level, the average level, the good level, and the very good level). After processing the results obtained statistically, it was found that the sample falls within the acceptable level of strategic management. The researcher concluded that the sample it has a good level of strategic management, and this is what has been identified by comparing the arithmetic mean with the hypothetical mean, which was less than the arithmetic mean of the research sample. Therefore, the researcher recommended the need to pay attention to the strategic management of the administrative bodies of the clubs of Babylon Governorate by involving them in training courses to prepare successful administrators According to a successful planning strategy.